Effect of organic selenium on the cooled boar semen quality and reproductive performance - Pavaneli, Ana Paula Pinoti (2022)
Selenium is an essential trace mineral for sperm development and maturation, acting as a modulator of sperm production and quality and male fertility. In pigs, inorganic selenium sources such as sodium selenite (SS) have been widely used to supplement diets, aiming to meet the nutritional requirements of each animal category within the production system. Considering the greater bioavailability of organic sources, the present study aimed to evaluate the use of hydroxy-selenomethionine (OH-SeMet) in the boars’ diet, a pure and organic source of selenium, on their semen characteristics and reproductive performance. It also evaluated two supplementation levels of OH-SeMet. For this, 42 purebred boars (Large-White and Landrace) aged 8 to 31 months were fed with the following dietary treatments during 95 days: 0.3 mg selenium/kg as SS (n = 14); 0.3 mg selenium/kg as OH-SeMet (n = 14); and 0.6 mg selenium/kg as OH-SeMet (n = 14). During this period, two experiments were carried out concurrently. In experiment 1, raw semen was evaluated for volume, sperm concentration, motility and morphology, and activity of the enzyme glutathione peroxidase (GPx) in seminal plasma. Semen doses were processed, stored at 17ºC for 72 h, and after that, evaluated for sperm quality (motility characteristics, morphology, integrity of membranes, and resistance to oxidative stress). The concentration of selenium in the seminal and blood plasma of the animals was also quantified. Semen collections occurred weekly, while experimental analyzes were carried out every 2 weeks, totaling 7 evaluation points during the study. In experiment 2, a total of 1131 purebred females (Large-White and Landrace) were inseminated with doses from the different treatments to assess the pregnancy rate (PR) and litter characteristics. Inseminations occurred throughout the experimental period (95 days), with semen doses sent to the farms weekly. The effects of the source (SS vs. OH-SeMet) and organic supplementation level (0.3 vs. 0.6 mg selenium/kg) were evaluated in both experiments. Boars fed OH-SeMet had more selenium in their seminal plasma (p<0.05), as well as tended (p<0.10) toward a higher total sperm count in the ejaculate (66.6 vs. 56.57 × 109 ) and, consequently, for an improvement on the number of semen doses produced (22.11 vs. 18.85). No effect was observed on selenium concentration in blood plasma, GPx activity in seminal plasma, and sperm quality in raw and stored semen (p> 0.05). On the farms, semen doses from the OH-SeMet group resulted in higher PR (99.3 vs. 97%) and fewer stillborn piglets (5.87 vs. 7.11%) (p<0.05). Regarding the use of different levels of OH-SeMet supplementation, no difference was observed between the values studied (p>0.05). In conclusion, replacing SS with OH-SeMet in the boars’ diet increases selenium availability in their reproductive system, seems to improve sperm production and results in better reproductive performance when semen doses are used on the farms.